Adapalene In The Treatment Of Acne Vulgaris - Prasad H R Y; Sharma Vinod K (Wolters Kluwer Medknow Publications, 2004)
Topical tretinoin, a retinoid long in use for the treatment of acne vulgaris, has the disadvantage of skin irritation. Adapalene, a third generation retinoid, has been claimed to have less side-effects. We evaluated the safety and efficacy of adapalene in an open uncontrolled trial. Thirty three patients of mild to moderate acne vulgaris were included in the study. Of them, 22 patients completed the study period of 12 weeks. The mean age of all 33 patients was 19 year with male to female ratio of 1.75:1. There was significant decrease in lesion count in each of 1,4,8 and 12 weeks evaluations (p <0.05) in both inflammatory and non-inflammatory lesions. About 70% complained of burning, 60% of itching and 30% of dryness. However, none of the side-effects was severe enough to stop the medication except in one case.